MIND MAPPING BASED JOYFULL LEARNING TO INCREASE WRITING SKILL - Dian Kusuma Dayu; Septi Aprilia (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2022)
This study aims to find out the differences in writing skills in elementary schools by using Mind Mapping-based Joyful learning models and determining the effectiveness of using Mind Mapping-based Joyful learning models in Indonesian writing skills. This research method is included in experimental research, which takes two groups as research samples. One group as an experimental class was given Mind Mapping-based Joy full learning models, and one group as a control class using the lecture and discussion method. Data analysis was performed using a T-test. The results of data analysis is Mind Mapping based Joyful learning models effectively teaches Indonesian writing skills in elementary school.